The Role of Influencers in Political Communication: Influence and Challenges of Collaboration with Public Figures - Dharta, Firdaus Yuni; Zou, Guijiao; Jie, Lie (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
The phenomenon of influencers in political communication has undergone development in the digital era. The use of influencers as a medium to convey political messages not only changes the paradigm of traditional communication but also creates new dynamics in the interaction between the public and political figures. The involvement of influencers in political campaigns shows great potential in influencing public opinion. This research aims to examine the role of influencers in political communication, particularly in the context of their influence on public opinion and the challenges faced in collaboration between influencers and public figures or politicians. The main focus is to understand how influencers influence political decisions and the implications of using influencers in political communication strategies. This study uses qualitative methods with a case study approach. The results show that influencers play a crucial role in shaping political narratives and influencing public opinion. Their influence is particularly evident in raising awareness of political issues and mobilizing young voters. However, the study also reveals significant challenges, including credibility issues and potential information bias that can affect public trust in the political process. The study concludes that while using influencers in political communication offers new opportunities for public engagement, it also requires a careful approach to managing the associated risks and challenges. Political parties and candidates need to choose influencers who have a wide reach and high credibility and integrity to maintain public trust and enhance the effectiveness of political communication.